Analysis of the behavior of concrete, steel fibre reinforced concrete and synthetic fiber reinforced concrete - Mabena, Abednigo Nkosinathi (Univerzita Pardubice, 2014)
The main objective of this thesis is to examine and compare the strength of conventional concrete and fiber-reinforced concrete i.e. steel fiber-reinforced concrete and polypropylene fiber reinforced concrete and to evaluate the correlation between the compressive strength and non-destructive testing methods. The scope of this work is divided into two parts, the theoretical part and experimental part. The theoretical part deals with the literature review on concrete as a construction material with the main focus being on the possible solutions for the concrete problems in the transportation infrastructure within the South Africa's context and abroad. The experimental part focuses on the production of concrete tests specimens, the analysis of concrete strength when exposed to extreme temperatures as well as the evaluation of the test results.
Analýza chování betonů, drátkobetonů a vláknobetonů
Keywords: beton; ocelová vlákna; polypropylenová vlákna; pevnostní zkoušky; concrete; steel fibers; polypropylene fibers; strength tests